Environmental Epidemiology of Sporadic Parkinson’s Disease - Chen, MD, PhD, Honglei; Huang, MD, PhD, Xuemei (North American Journal of Medicine and Science, 2010)
Parkinson’s disease (PD) is the second most prevalent neurodegenerative disease of the elderly. The causes of PD are largely unknown, but probably involve both genetic and environmental factors. Breakthroughs have been made in the past decade to identify genes that are responsible for early-onset familial PD, yet the role of genes in sporadic PD needs to be defined. Twin studies suggest that environmental factors may be crucial in determining the risk of late-onset sporadic PD. To date, strong epidemiological evidence links environmental factors like cigarette smoking and coffee drinking to a lower PD risk, and to a lesser extent, pesticide exposures to a higher PD risk. Several novel findings have emerged from recent prospective studies on PD, such as a positive association with consumption of dairy products, and an inverse relationship with plasma urate concentration. Although gene-environment interactions are thought to be important in PD etiology, they rarely have been investigated. In the search of environmental PD risk factors, future multidisciplinary research is needed that includes input from both genetics and experimental biology. Interaction analysis requires information on both environmental and genetic factors from a large population, and such future studies will benefit from collaborative pooled analysis.